A Critical Discourse Analysis of the Representation of Local Culture in Indonesia’s EFL Textbook - Izzah, Uzlatul; Basya, Dihliza; Nugraheni, Dyah Ayu (English Teaching Journal : A Journal of English Literature, Language and Education, 2024)
Although numerous studies have explored cultural elements in EFL textbooks, there is a lack of research on the inclusion of Indonesian local culture in EFL textbooks following the autonomous curriculum. Thus, this study utilizes the autonomous curriculum English as a Foreign Language (EFL) textbook employed in Indonesia to examine the portrayal of local culture within it. Through Critical Discourse Analysis (CDA) (Fairclough, 2013), researchers want to know the extent of local cultural representation contained in EFL textbooks. This research employs systemic functional analysis, a method that Halliday and Matthiessen (2014) originally devised, to analyze textual data (dialogue, worksheet instruction, and article) contained in EFL textbooks. In addition, visual data is analyzed in accordance with Kress and Van Leeuwen's Visual Grammar Theory (2021). The scope of this research is limited to the depiction of Indonesian local culture in a selected Indonesian EFL textbook that is officially published and utilized within the nation. The results show that local Indonesian culture is integrated in EFL textbooks visually and textually, with elements of local culture that are often found in textbooks, as it mainly focused on the traditions, values and symbols of Indonesian life.